Synergistic effects of CdS QDs – Neutral red dye hybrid system on its nonlinear optical properties. (October 2021) - Kuriakose, Alina C.; Udayan, Sony; Priya Rose, T.; Nampoori, V.P.N.; Thomas, Sheenu
Highlights: We presented the nonlinear optical properties of CdS-NR hybrid system. Enhanced nonlinear optical properties was observed with the hybrid. CdS-NR showed enhanced optical limiting response. Synergistic effects of TPA and ESA contributed towards the enhanced properties. Abstract: One of the main goal in the area of nanophotonics is to reinforce the nonlinear optical effects at low input fluence. In this regard, nanohybrids have received special attention which render remarkable third-order nonlinear optical properties. Herein, we have studied the nonlinear optical properties of CdS Quantum Dots (QDs) - Neutral Red (NR) nanohybrid system using Z-scan technique and report the development of functional materials for optical limiting applications. Open aperture Z-scan results suggests that reverse saturable absorption is the predominant mechanism behind the observed nonlinear effects and it can be ascribed to enhanced triplet state population. A significant enhancement in the nonlinear absorption coefficient, nonlinear refraction and third-order nonlinear susceptibility is observed with the nanohybrids as compared to their individual components. The enhanced nonlinear properties can be attributed to cumulative effects of distinct nonlinear mechanisms.